Enhancing oneself with an exosense: Learning from users' experiences. Issue 4 (4th October 2019) - Gauttier, Stéphanie
Abstract: The literature on human enhancement has long been limited to the fields of bioethics and philosophy, confining itself to an ideological battle. However, scholars have called for empirical data to move the debate forward. While there is a nascent literature on attitudes toward the human enhancement technology, there has been no scholarly examination of the experience of enhancement. Yet, risks and ethical issues reveal themselves through use. This paper focuses on a new form of cyborg technology for cognitive enhancement on the market: exosenses, that is, external senses. Three cases of the use of exosenses are presented. The experience of exosense users is analyzed based on interviews published in the media and videos posted by the users themselves. A thematic analysis is conducted. The different dimensions of the experiences are revealed. The first one pertains to defining augmentation, the second one is the natural character of exosenses, third one is the impact that the exosense has on real life, the fourth theme is about personal identity and exosense, and finally, the fifth theme revolves around the risks and opportunities presented by the use of exosenses.